DESIGN OF STORAGE LPG TANK WITH ANALYSIS OF SLOSHING DUE TO EARTHQUAKE LOADING BASED ON SNI 03-1726-2012 - Putri Nabilah, Aldarifa
Due to its geographic position, Indonesia is prone to earthquakes. This makes seismic based analysis essential in designing large storage tanks, beside other loading. The effect of earthquakes on large body of liquid being stored in an enclosed area is the increased risk of inducing a phenomenon called sloshing. Sloshing is the motion of a fluid inside a container that was caused by erratic random acceleration on the fluid container itself. This sloshing motion may cause high forces on the tank structure that could lead to disaster. In this study, an 80.005 m³ LPG storage tank is being designed based on seismic and thermal loadings using two approaches, namely “design by code” which refers to API 620, and “design by analysis” which refers to API 650 Appendix E for the analysis method and SNI 02-1726-2012 for the seismic loading. “Design by analysis” is carried out in two stages, starting with fluid dynamics modeling to determine the fluid response at natural periods and maximum acceleration, and then followed by strength analysis of the tank due to dynamic fluid loads. Heat transfer analysis is performed analytically to determine the boil-off gas rate in the tank. Based on the design by code, the tank wall thickness ranges from 10 mm to 30 mm for A537-CL2+S5 material. According to the heat transfer analysis, the boil-off gas rate is 0.042 wt%/day with an insulation thickness of 0.7 m consisting perlite powder and resilient blanket. The design by analysis shows an increase in hoop stress by 24.5% under loading based on the natural period. Under maximum acceleration loading, there is a 43% increase in hoop stress exceeds the maximum allowable increase of 40%.